Reframing The Period Of The Sahaba And Tabi`In In The Archipelago: Acceptance Of Tradition - Hasbi, Ridwan; Rehayati, Rina; Martius, Martius; Kuakul, Yuttana (Jurnal Ushuluddin, 2024)
The presence of the Sahaba and Tabi`in in the archipelago is proven by the discovery of grave sites and historical records that corroborate the Arab theory of the entry of Islam. The period of the Sahaba and Tabi`in was the period that received the best certification from the Prophet with the phrase "Khair al-Qurun". This hadith becomes the basis for the continuity of traditions carried out by the Moslim archipelago, which cannot be separated from the assimilation and acculturation carried out by the Sahaba and the Tabi`in. This research uses qualitative methods that are formulated in historical and interconnection aspects. The elaboration of this method is related to content analysis that correlates with the descriptive hadith of the Prophet about the virtues of the period of the Sahaba and the Tabi`in. The movement of the Sahaba as the successor of the Prophet and followed by the Tabi`in in spreading the mission of preaching Islam throughout the world was assimilated with the traditions that already existed in the region. The revitalization of the framing of the period of the Sahaba and Tabi`in in the archipelago is related to the understanding that the period of the Sahaba and Tabi`in was only in the Arabian Peninsula. The thought is dismantled in the facts and data that the period of the Sahaba and Tabi`in existed in the archipelago as a construction that the Moslem religion is now going straight with the teachings of Islam